Cost of Living Adjustment and Business Cycles : Disaggregated Evidence - Kandil, Magda (Washington, D.C. : International Monetary Fund, 2000)
For a sample of US industries, nominal wage and price inflation follow aggregate price inflation closely during economic expansions. Hence, fluctuations in profit markup and real output are moderate in the face of expansionary demand shocks. During recessions, however, industrial nominal wage deflation exceeds that of the aggregate price level. This is in contras to producers' attempt to maintain, or even increase, industrial real price inflation during recessions. Consistently, the increase in the profit markup is correlated with an increase in output contraction and a reduction in workers' real standard of living during recessions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet